Imaging Recommendations for Diagnosis, Staging, and Management of Esophageal Cancer - Chakrabarty, Nivedita; Mahajan, Abhishek; Patil, Prachi; Chowhan, Manoranjan; Munmmudi, Naveen; Niyogi, Devayani; Dabkara, Deepak; Singh, Suryaveer; Singh, Ajaykumar; Devarmani, Sanjana; Dhull, Varun Singh; Prabhash, Kumar (Indian Journal of Medical and Paediatric Oncology, 2023)
Early staging and treatment initiation affect prognosis of patients with esophageal and esophagogastric junction cancer; hence, it is imperative to have knowledge of proper choice of imaging modality for staging of these patients, to effectively convey relevant imaging findings to the treating physician/surgeon. It is also essential to be aware of pertinent imaging findings that need to be conveyed to the treating physician/surgeon at staging, and after treatment, including post-therapy complications (if any), so as to provide timely management to such patients. In this article, we have provided imaging guidelines for diagnosis, staging, post-therapy response evaluation, follow-up, and assessment of post-therapy complications of esophageal and esophagogastric junction cancer in a systematic manner. Besides, risk factors and clinical workup have also been elucidated. We have also attached comprehensive staging and post-therapy contrast-enhanced computed tomography and fluorodeoxyglucose-positron emission tomography/computed tomography-based synoptic reporting formats “ECI-RADS” and “pECI-RADS,” respectively, for esophageal and esophagogastric junction cancer in the supplement, for effective communication of imaging findings between a radiologist and the treating physician/surgeon.
Keywords: esophageal cancer; imaging guidelines; staging; post-therapy; synoptic reporting formats